1998
DOI: 10.1111/j.1440-1770.1998.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of compensatory and additive mortality to the management of selected sportfish populations

Abstract: The compensatory mortality hypothesis postulates that a population's total mortality remains unchanged at low to intermediate exploitation rates because natural mortality decreases to compensate for reduced density, whereas the additive mortality hypothesis postulates that any increase in exploitation mortality results in an increase in total mortality. Fishing and natural mortality rates have generally been assumed to be additive rather than compensatory. We reviewed mortality estimates for some prominent spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 33 publications
3
78
0
Order By: Relevance
“…These yield models are based on the assumption that natural and fishing mortality rates are additive rather than compensatory. This assumption is supported by a review of published estimates of exploitation and total mortality rates for largemouth bass (Allen et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…These yield models are based on the assumption that natural and fishing mortality rates are additive rather than compensatory. This assumption is supported by a review of published estimates of exploitation and total mortality rates for largemouth bass (Allen et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…By assuming 0% tag loss, managers are underestimating exploitation and fishing mortality rates and thus overestimating natural mortality rates. Fishing and natural mortality rates are generally accepted to be compensatory risks of death for certain fish species, i.e., natural mortality decreases as fishing mortality increases (Allen et al 1998). By overestimating natural mortality, managers might believe that exploitation and fishing mortality can be increased, thereby leading to overfishing of the stock.…”
Section: Discussionmentioning
confidence: 98%
“…Although lake productivity was only a marginally important variable in the relationship between density and growth for the Minnesota lakes data, it became more significant in the pooled data. In a survey of the literature Allen et al (1998) found exploitation may be compensatory for pike less than 40 cm total length (cannibalism was reduced; natural mortality decreased to compensate for the exploitation and total mortality remained near constant) but became additive (i.e. total mortality increased) in larger fish.…”
Section: Population Dynamicsmentioning
confidence: 95%